Effects of propofol on cardiac function and miR-494 expression in rats with hepatic ischemia/reperfusion injury. Issue 3 (March 2021) - Lv, Jie; Zou, Xiaohua; Yu, Chao; Ou, Wei; Sun, Chengyi
Objective: This study aimed to investigate the effects of propofol on cardiac function and miR-494 expression in rats with hepatic ischemia/reperfusion (I/R) injury. Methods: Forty healthy adult male Sprague-Dawley rats were allocated to the sham operation group and three hepatic I/R injury groups. The I/R injury groups included I/R injury only (I/R group), treatment with propofol (propofol group), and treatment with propofol + overexpressed miR-494 (propofol+miR-494 group). Apoptosis of myocardial cells and changes in cardiac function indices, including left ventricular end-diastolic diameter, left ventricular end-systolic diameter, and left ventricular posterior wall thickness, as well as changes in miR-494, were monitored. Results: The apoptotic rate of myocardial cells in the I/R group was higher, cardiac function was deteriorated, and miR-494 levels were elevated compared with the sham group. The apoptotic rate was lower, cardiac function was improved, and miR-494 levels were suppressed in the propofol group compared with the I/R group. The apoptotic rate was higher, cardiac function was deteriorated, and miR-494 levels were elevated in the propofol+miR-494 group compared with the propofol group. Conclusion: Propofol plays a vital role in preventing myocardial cell apoptosis and improvement of cardiac function by suppressing miR-494 in a hepatic I/R injury rat model.